Study on Chess-Sinthome: A New Approach to Bobby Fischer´s Psychosis - Jorge Luis Zirulnik; Miguel Angel Pagano (Current Topics in Medicine and Medical Research Vol. 12, 2021)
The psychology of chess players has called the attention of several researchers for more than a century. There is a notable lack of scientific works with a plausible hypothesis about Bobby Fischer´s paranoid psychosis and its relationship with his prodigious performance. In this brief theoretical work, a new conceptual model is proposed to explain the psychosis of American chess player Bobby Fischer. Based on the pioneering work of psychoanalysts, we introduce the concept of sinthome, taken from the Lacanian topology of the Borromean knot, with its three registers: Real, symbolic and imaginary [RSI], and its fourth stabilizer knot at the breaking of the symbolic. Here we call it chess-sinthome to designate the antipsychotic role fulfilled the ultra-competitive chess, in life and in the minds of some great players. This category of chess sinthome that was brought to our analysis by lacanian theory could be presented as a new second-generation paradigm to explain Bobby Fischer´s psychosis, after the pioneering works were already studied. The ability to predict its clinical appearance in the near future shall be a fascinating perspective.